Knowledge about, attitude toward, and practice of complementary and alternative medicine among nursing students: A systematic review of cross-sectional studies - Zhao, Fei-Yi; Kennedy, Gerard A.; Cleary, Sonja; Conduit, Russell; Zhang, Wen-Jing; Fu, Qiang-Qiang; Zheng, Zhen (Frontiers in Public Health, 2022)
Background The globally growing demand for complementary and alternative medicine (CAM) has attracted educators’ attention to integrate CAM into conventional nursing programs. This systematic review aimed to understand the status quo of nursing students (NSs)' overall rated knowledge of, attitude/belief towards, and practice/previous use or experience (KAP) of CAM in surveys, given these factors may influence NSs' receptivity to CAM curricula, and may be of value in guiding the development of effective teaching strategies. Methods Formally published cross-sectional quantitative studies investigating the primary outcome of KAP towards CAM by NSs were searched for from eight databases from launch through to April 2022. PRISMA 2020 guidelines were followed. Results Twenty-six studies were included for analysis, 25 of which were judged to be of moderate to high quality. Despite limited and poorly informed knowledge of CAM therapies, the majority of NSs generally viewed them in a positive light. Lack of evidence was perceived as a major barrier to the use or integration of CAM. Mass media and the internet were the main sources in which NSs access CAM information. Measurement of KAP in all included studies was via self-designed questionnaire/scale or adapted from previously developed questionnaires. Conclusions Current evidence indicates that NSs generally lack adequate CAM knowledge and would welcome integration of CAM curricula, at least as elective modules, into existing nursing programs. Besides theoretical knowledge and matched clinical placement, skills training in literature search and evidence-based practice are advised to be included in the curricula design. Experiential learning mode is strongly recommended in delivering specific CAM modalities. In addition, a standard instrumentation for determining NSs' KAP towards CAM should be designed and examined for use in different cultural settings.